The Effect of RPG Maker Mobile Learning Model in Learning English - Afief Fakhruddin; Abdur Rasyid (Universitas PGRI Semarang, 2023)
The aimed of this research was to measure the effect of application (RPG) MakerMV. This research belongs to experimental research and quasi experimental design. It described about the effect of using of the application. The research methodology was a quantitative method. The population of this study was one Class XI students from MA Siti Khadijah, and the sample was twenty students or two classes throughpurposive sampling. The research result showed that this application were very effective and very easy to use.The researcher concluded that the experimental group through this application in the right way. The average percentage of student activity is 75.6%, which is included in both categories.The experimental group had higher score (429) after learning English vocabulary using direct method than control group (274). The conclusions of this study was RPG Maker mobile effective in the teaching learning English. This study recommended to use this aplication in teaching english. The application help students to follow the lesson